Magnetic Force Microscopy on Nanofibers—Limits and Possible Approaches for Randomly Oriented Nanofiber Mats - Andrea Ehrmann (MDPI AG, 2021)
Magnetic force microscopy (MFM) belongs to the methods that enable spatially resolved magnetization measurements on common thin-film samples or magnetic nanostructures. The lateral resolution can be much higher than in Kerr microscopy, another spatially resolved magnetization imaging technique, but since MFM commonly necessitates positioning a cantilever tip typically within a few nanometers from the surface, it is often more complicated than other techniques. Here, we investigate the progresses in MFM on magnetic nanofibers that can be found in the literature during the last years. While MFM measurements on magnetic nanodots or thin-film samples can often be found in the scientific literature, reports on magnetic force microscopy on single nanofibers or chaotic nanofiber mats are scarce. The aim of this review is to show which MFM investigations can be conducted on magnetic nanofibers, where the recent borders are, and which ideas can be transferred from MFM on other rough surfaces towards nanofiber mats.